Makna Simbolik Dalam Naik Garudo Oleh Pengantin Pada Upacara Pernikahan Adat Melayu Jambi - Viona Audia Putri, Junita Yosephine Sinurat (LP4MK STKIP PGRI Lubuklinggau, 2025)
Culture is emotion, creativity and intention. Culture is the result of human production itself. Culture always coexists with tradition. This research aims to determine the symbolic meaning of wedding traditions in the Malay community in Jambi, Mersam District. Garudo riding is a community tradition in Mersam District, Mersam District, Jambi City. We can see the Naik Garudo tradition at weddings or during the procession of the bride and groom during the day. The research methodology used in writing this research consists of four stages, namely elicitation, source criticism, interpretation, and historiography. The types of sources used in writing this research are library research and technical historical analysis using interpretation of historical facts which include books, documents and journals related to Jambi Malay customs. The results of this research are that